Health Security Protection For Indonesian Migrant Workers: A Ministerial Regulation Perspective - Puspitasari, Eva (Journal of Law and Policy Transformation, 2023)
Migrant workers are an asset for the country because they make many good contributions to the country. Just like other citizens, migrant workers have the right to access social security, especially health, in their country of placement. However, in reality access to health insurance in the host country is still limited due to the absence of technical regulations that specifically regulate this situation. Apart from that, the current policies are not yet able to protect migrant workers due to the lack of clarity regarding technical protection, which affects migrant workers' compliance in paying mandatory health insurance contributions. Therefore, this research will discuss in more detail the provision of social health security for migrant workers. The formulation of the problem studied in this research is what is the ideal health insurance protection policy for Indonesian Migrant Workers abroad? And how to strengthen the commitment to protect the health insurance of Indonesian Migrant Workers abroad in their country of placement? The research method used in this research is a normative legal method with statutory, case and conceptual approaches. This research finds that current policies do not provide good access for migrant workers, so policy reformulation is needed, one of which is a direct payment method from the government to the placement country. The strategy to strengthen commitment that can be carried out to provide good access to migrant workers is to make improvements in the legal system which includes substance, law enforcement and legal culture.